PENGARUH AKTIVITAS PERTAMBANGAN TERHADAP NILAI PRODUK DOMESTIK REGIONAL BRUTO DAN EKONOMI MASYARAKAT DI PROVINSI KALIMANTAN TIMUR - Putri, Wahyu Endah Christiani; Zamroni, Akhmad; Widiatmoko, Fajar Rizki (KURVATEK, 2020)
Gross Regional Domestic Product (GRDP) is a macroeconomic indicator of the economic condition in a region. The development of GRDP per capita is often used as an indicator of a region’s success in economic development. One of the economic sectors that is an indicator of the success of regional development is the mining and excavation sector. East Kalimantan Province is a province with a wealth of natural resources in the form of coal mining. The purpose of this study is to analyze the effect of mining activities in East Kalimantan on the value of the GRDP and the economic conditions in that region. The results showed that mining activities had a significant effect on the GRDP per Capita and the economic conditions of the people in East Kalimantan Province. GRDP according to mining and excavation fields has an effect of 0.9431 on GDP per capita in East Kalimantan Province. The number 0.9431 in statistics means that the X coefficient has a strong effect on the Y coefficient. All decreases and increases in mining and excavation fields have a significant and proportional effect on the economic conditions of the people in East Kalimantan Province. Keywords: Gross Regional Domestic Product (GRDP), mining, economic conditions, East Kalimantan.